Managing organizations for sustainable development in emerging countries: an introduction - Gunasekaran, Angappa; Chiappetta Jabbour, Charbel Jose [UNESP]; Lopes de Sousa Jabbour, Ana Beatriz [UNESP] (Taylor & Francis Inc, 2014)
This introduction article is for the special issue Managing organizations for sustainable development in emerging countries: natural resources, biodiversity, and climate change' in the International Journal of Sustainable Development & World Ecology and presents an introduction to the topics and summarizes accepted contributions in the special issue. The accepted works may contribute with organizational management in the search for more sustainable organizations. The works focus on the challenges of managing organizations in a context of degradation of natural resources, loss of biodiversity, and climate change. Accepted papers discuss these issues, based on the reality of emerging economies (e.g. Brazil, India, and China).
Keywords: natural resources; biodiversity; climate change; emerging economies; sustainable development